(untitled) (Research, Society and Development, 2022)
Carbohydrate is considered as the main source of energy for living beings because its substrates are used by several metabolic pathways responsible for energy production in the body. The consumption of certain macronutrients at specific times in relation to the training time is one of the main strategies used in sports nutrition. The present study aims to analyze the effects on physical and sports performance with the use of carbohydrates in the pre-workout meal. This is an integrative review of the literature available in the PubMed and Scielo databases, using the descriptors: “exercise”, “athletic performance” and “carbohydrates”. Only clinical trials published between 2016 and 2022 were included. After reviewing the literature, 12 studies were selected that evaluated, among other aspects, physical performance in different sports modalities using pre-exercise nutritional strategies that include carbohydrates in its composition. The results found suggest that the pre-workout consumption of carbohydrates can improve performance in strength exercises, but not in aerobic exercises.